2016
DOI: 10.1007/s11248-016-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel heavy metal ATPase peptide from Prosopis juliflora is involved in metal uptake in yeast and tobacco

Abstract: Heavy metal pollution of agricultural soils is one of the most severe ecological problems in the world. Prosopis juliflora, a phreatophytic tree species, grows well in heavy metal laden industrial sites and is known to accumulate heavy metals. Heavy Metal ATPases (HMAs) are ATP driven heavy metal pumps that translocate heavy metals across biological membranes thus helping the plant in heavy metal tolerance and phytoremediation. In the present study we have isolated and characterized a novel 28.9 kDa heavy meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…On the other hand, the abundance of Pb and Cd, the less concentrated metals in the growth medium independent of the sewage sludge content, were similar among treatments in the leaves and roots, except for Cd in roots for the highest sewage sludge contents. This may be related to the presence of a transport peptide in this species that seems to have an important role in Cd uptake [47]. In contrast, the concentration of Cu, Zn, Cr, Ni, Co, and Fe in leaves and roots increased with the addition of sewage sludge.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the abundance of Pb and Cd, the less concentrated metals in the growth medium independent of the sewage sludge content, were similar among treatments in the leaves and roots, except for Cd in roots for the highest sewage sludge contents. This may be related to the presence of a transport peptide in this species that seems to have an important role in Cd uptake [47]. In contrast, the concentration of Cu, Zn, Cr, Ni, Co, and Fe in leaves and roots increased with the addition of sewage sludge.…”
Section: Discussionmentioning
confidence: 93%
“…There are three processes of Cd transport in plants: root absorption, long-distance transport to the aboveground parts, and storage in leaves. Cd and its chelate-related transporters mainly include zinc/iron transporters (ZRT/IRT-like protein, ZIP) [ 61 ], natural resistance-associated macrophage proteins (NRAMPs) [ 62 ], HMAs [ 63 ], metal tolerance proteins (MTP), a cation exchanger (CAX) [ 64 ], an ATP binding cassette transporter (ABC) transporter [ 65 ], and a yellow stripe-like transporter (YSL) [ 66 ]. By analyzing the expression of genes related to Cd absorption and transport, we found that the expression level of most members of ZIP, HMAs, NRAMPs, CAX, YSL, and MTP families was upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperone is an important way in delivering Cu to heavy metal P1B-ATPases [41]. In general, HMA contain approximately 6-8 transmembrane helices, a soluble nucleotide binding domain, phosphorylation domain, and a soluble actuator domain, of which HMA1-4 belonging to Zn 2+ /Co 2+ /Cd 2+ /Pb 2+ transporting, although HMA1 conserved amino acids is different from the HMA2, HMA3 and HMA4 [33], whereas HMA5-8 belong to the Cu + /Ag + subclass [51].…”
Section: Discussionmentioning
confidence: 99%
“…HMA (Heavy Metal ATPase) belonging to P1B-type ATPases (also called CPx-ATPases), is responsible for ion detoxi cation/transport [32,33,34] and vacuolar compartmentalization [35,36]. It is interesting in double mutant that HMA not only affects the transport of heavy metals [37], but also affect the plant growth and development [34].…”
Section: Introductionmentioning
confidence: 99%